2014
DOI: 10.1093/scan/nsu025
|View full text |Cite
|
Sign up to set email alerts
|

Harm avoiders suppress motor resonance to observed immoral actions

Abstract: Motor resonance (MR) contingent upon action observation is thought to occur largely automatically. Although recent studies suggest that this process is not completely impervious to top-down modulations, much less is known on the possible role of the moral connotation of observed action goal in modulating MR. Here, we explored whether observing actions with different moral connotations modulates MR and whether any modulation depends on the onlookers' personality. To this aim, we recorded motor potentials evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…In fact, the delay found in response to the Arabian outgroup member as he moved toward a gun can be interpreted as a freeze reaction to a harmfully perceived event as suggested by several studies that show that spontaneous body responses to social threat cues elicit freeze-like behaviors in humans (Roelofs et al, 2010). Moreover, our findings are in line with previous studies on the effects of morality on MR (Liuzza et al, 2015) showing a decrease in MR when observing immoral actions, in particular in individuals presenting high levels of harm avoidance. As an extension of this work, it will be interesting to investigate the relation between MR and visual attention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, the delay found in response to the Arabian outgroup member as he moved toward a gun can be interpreted as a freeze reaction to a harmfully perceived event as suggested by several studies that show that spontaneous body responses to social threat cues elicit freeze-like behaviors in humans (Roelofs et al, 2010). Moreover, our findings are in line with previous studies on the effects of morality on MR (Liuzza et al, 2015) showing a decrease in MR when observing immoral actions, in particular in individuals presenting high levels of harm avoidance. As an extension of this work, it will be interesting to investigate the relation between MR and visual attention.…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, we expected that social threat elicited by a specific outgroup (i.e., stereotypically aggressive) in a specific context (i.e., threatening contextual cues) is likely to amplify the pattern. This hypothesis is in line with previous studies on the effect of morality on MR (Liuzza et al, 2015), which shows that the phenomenon is significantly reduced when observing immoral actions (namely actions related to social threats; Brambilla et al, 2013) in individuals presenting high levels of harm avoidance.…”
Section: Introductionsupporting
confidence: 91%
“…As expected, participants made fewer egoistic lies to high than low‐warmth individuals, supporting the idea that moral information is of primary importance in guiding social judgements and interpersonal behaviour (Brambilla, Rusconi, Sacchi, & Cherubini, ; Delgado et al ., ; Liuzza, Candidi, Sforza, & Aglioti, ; Mancini, Betti, Panasiti, Pavone, & Aglioti, ; Panasiti, Puzzo, & Chakrabarti, ; Willis & Todorov, ; Wojciszke et al ., ). These results expand previous evidence that people tend to trust (Delgado et al ., ) and cooperate (Steinel & De Dreu, ) more with warm individuals, by showing that inferred warmth reduces the tendency to deceive others.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating the perceptual and personality domain, a recent TMS study showed that interhemispheric connectivity was related to an attentional bias to angry facial expressions and to an aggressive personality style (Hofman & Schutter, 2009). As effects of personality on motor corticospinal excitability levels have also been reported (Avenanti, Minio-Paluello, Bufalari, & Aglioti, 2009;Liuzza, Candidi, Sforza, & Aglioti, 2015;Wassermann, Greenberg, Nguyen, & Murphy, 2001), future studies may incorporate measures of aggression-and/or anxiety-related traits in the study of perception and interpretation of threat and the occurrence of defensive and/or aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%